Well-preserved arboreal microhabitats in a highly urbanized landscape can support populations of specialized saproxylic hoverflies (Diptera: Syrphidae) - Maritano, Umberto (Fragmenta entomologica, 2023)
New saproxylic hoverfl y data are reported from a survey in University Campus Park, Grugliasco (North-western Italy) with implications for the conservation of arboreal microhabitats in highly urbanized landscapes.